Persepsi penganut Muslim dan bukan Muslim terhadap isu-isu sensitif agama: kajian di Lembah Klang - Nur Farhana Abdul Rahman,; Nur Syarihah Muhammad Shah, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Religious sensitive issues are frequently raised in the Malaysia community whether by Muslims or non-Muslims. The rise of these issues could affect the peace and harmony of the country if it is not well handled. Therefore, this article aims to examine the perceptions of religious people in the Klang Valley on issues of religious sensitivity as well as explaining the level and factors of religious sensitivity. The study used quantitative methods through the distribution of questionnaires to 384 respondents living in the Klang Valley, namely, Selangor, Kuala Lumpur and Putrajaya. The respondents consisted of Muslims, Buddhists, Hindus and Christians. The findings of the study were descriptively analyzed using frequency, percentage, mean and standard deviation. The study found that the most sensitive issue in theological context was the contempt of the scriptures or religious practices, in the social context was the act of doing damage to the synagogue while in the context of ethics it was an insult to the body or body of the religious. The level of religious sensitivity reported to be high on matters of theology and ethics but on social matters, it is at a moderate level. This indirectly indicates that matters affecting theology and ethics are more sensitive than social matters. Studies have also reported that the biggest obstacle to maintaining religious sensitivity is social media as the platform often presents news of religious tensions leading to prejudice among people of various religions.